Sustained Local Release of Methylprednisolone From a Thiol-Acrylate Poly(Ethylene Glycol) Hydrogel for Treating Chronic Compressive Radicular Pain. Issue 8 (April 2016) - Slotkin, Jonathan R.; Ness, Jennifer K.; Snyder, Kristin M.; Skiles, Amanda A.; Woodard, Eric J.; O'Shea, Timothy; Layer, Rick T.; Aimetti, Alex A.; Toms, Steven A.; Langer, Robert; Tapinos, Nikos
Abstract : Study Design: A preclinical animal model of chronic ligation of the sciatic nerve was used to compare the effectiveness of a slow-release hydrogel carrying methylprednisolone to methylprednisolone injection alone, which simulates the current standard of care for chronic compressive radiculopathy (CR). Objective: To extend the short-term benefits of steroid injections by using a nonswelling, biodegradable hydrogel as carrier to locally release methylprednisolone in a regulated and sustained way at the site of nerve compression. Summary of Background Data: CR affects millions worldwide annually, and is a cause of costly disability with significant societal impact. Currently, a leading nonsurgical therapy involves epidural injection of steroids to temporarily alleviate the pain associated with CR. However, an effective way to extend the short-term effect of steroid treatment to address the chronic component of CR does not exist. Methods: We induced chronic compression injury of the sciatic nerves of rats by permanent ligation. Forty-eight hours later we injected our methylprednisolone infused hydrogel and assessed the effectiveness of our treatment for 4 weeks. We quantified mechanical hyperalgesia using a Dynamic Plantar Aesthesiometer (Ugo Basile, Stoelting Co., IL, USA), whereas gait analysis was conducted using the Catwalk automated gait analysis platform (Noldus, Leesburg, VA, USA). Macrophage staining was performed with immunohistochemistry and quantification of monocyte chemoattractant protein-1 in sciatic nerve lysates was performed with multiplex immunoassay using a SECTOR Imager 2400A (Meso Scale Discovery, Rockville, MA, USA). Results: We demonstrate that using the hydrogel to deliver methylprednisolone results in significant ( P  < 0.05) reduction of hyperalgesia and improvement in the gait pattern of animals with chronic lesions as compared with animals treated with steroid alone. In addition, animals treated with hydrogel plus steroid showed significant reduction in the number of infiltrating macrophages at the sciatic nerve and reduced expression of the neuroinflammatory chemokine monocyte chemoattractant protein-1 ( P  < 0.05). Conclusion: Use of hydrogels as carriers for sustained local release of steroids provides significantly better control of pain in an animal model of chronic CR. Our steroid-infused hydrogel could be an effective extender of the short-term benefits of epidural steroid injections for patients with chronic compression-induced radicular pain. Level of Evidence: N/A Abstract : Supplemental Digital Content is available in the text